2012
DOI: 10.1093/nar/gks1141
|View full text |Cite
|
Sign up to set email alerts
|

FlyAtlas: database of gene expression in the tissues of Drosophila melanogaster

Abstract: The FlyAtlas resource contains data on the expression of the genes of Drosophila melanogaster in different tissues (currently 25—17 adult and 8 larval) obtained by hybridization of messenger RNA to Affymetrix Drosophila Genome 2 microarrays. The microarray probe sets cover 13 250 Drosophila genes, detecting 12 533 in an unambiguous manner. The data underlying the original web application (http://flyatlas.org) have been restructured into a relational database and a Java servlet written to provide a new web inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
173
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(183 citation statements)
references
References 7 publications
9
173
1
Order By: Relevance
“…The online atlas of gene expression, FlyAtlas.org, shows that both Nha1 and Nha2 are widely expressed, but particularly in the epithelia of the alimentary canal (15,23,24). To validate this pattern of gene expression, we performed quantitative real-time PCR, which demonstrated consistent enrichment levels at least as high as those seen in the Affymetrix-derived FlyAtlas (Fig.…”
Section: Resultsmentioning
confidence: 85%
“…The online atlas of gene expression, FlyAtlas.org, shows that both Nha1 and Nha2 are widely expressed, but particularly in the epithelia of the alimentary canal (15,23,24). To validate this pattern of gene expression, we performed quantitative real-time PCR, which demonstrated consistent enrichment levels at least as high as those seen in the Affymetrix-derived FlyAtlas (Fig.…”
Section: Resultsmentioning
confidence: 85%
“…Specifically, nutrient absorption occurs primarily in the insect midgut (Ohlstein and Spradling 2006;Buchon et al 2013), which might be expected to respond most rapidly to oral toxin intake. To address the issue we used two metrics, TP(i) and TSr(i), both of which combine our expression data sets with data available in the FlyAtlas database (Chintapalli et al 2007;Robinson et al 2013), a unique resource with tissue expression data collected across several dissected tissues. We observed that neither treatment with high sugar nor that with DEHP showed an overtly tissue-specific disruption in either sets of upregulated ( Figure S5) or downregulated ( Figure 2A) genes.…”
Section: Resultsmentioning
confidence: 99%
“…Tissue specificity of differentially expressed (DE) genes was assessed using the FlyAtlas (Chintapalli et al 2007;Robinson et al 2013). We filtered the data to include only a nonredundant set of adult tissues: brain, eye, adult thoracicoabdominal ganglion (tag), adult salivary gland (sg), testis, accessory glands (acc), crop, midgut, tubule, hindgut, heart, and adult fat body.…”
Section: Metrics Of Tissue Perturbationmentioning
confidence: 99%
“…A total of 1,931,250 SNPs and indels were used in our analyses, with the minor alleles present in at least seven DGRP lines, using only biallelic sites. For each tissue, we used FlyAtlas AffyCalls (23) to determine which genes were expressed in which tissue. To determine significance, we used a Fisher's exact test comparing the expected number of gene expressed in each tissue across the entire genome to the observed number of genes expressed in each tissue in our gene list.…”
Section: Methodsmentioning
confidence: 99%